The method to develop classifi ers based on geometrical interpretation of data structure - М. N. Nessonova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The method of supervised classification is suggested in the article. The method allows developing mathematical models of algorithms for computing estimates. It is based on metric approach to representations, generated by statistical methods of geometric interpreting of data structure.